Association between bullying victimization and mental health problems among Chinese left-behind children: a cross-sectional study from the adolescence mental health promotion cohort - Feng, Yuan; Zhang, Simai; Liao, Xiao; Jia, Yuge; Yang, Yu (Frontiers in Psychiatry, 2024)
BackgroundLeft-behind children (LBC) refer to those who have been separated from at least one parent for six months or more due to parental migration for work. This phenomenon poses a significant threat to the mental health of over 61 million LBC in China. This study aims to compare the prevalence of mental health symptoms between LBC and non-left-behind children (non-LBC) and to explore the predictive effect of bullying victimization on adolescent mental health problems.MethodsIn 2019, we conducted a cross-sectional analysis involving 28,036 children and adolescents in Mianyang City, Sichuan Province, China, with ages ranging from 8 to 19 years. Mental health symptoms were assessed using the 7-item Generalized Anxiety Disorder (GAD-7) scale and the 9-item Patient Health Questionnaire (PHQ-9). The Delaware Bullying Victimization Scale-Student (DBVS-S) was employed to gather data on experiences of bullying victimization. Information on self-injury was collected by inquiring whether participants had engaged in self-injurious behavior and the reasons for such behavior. Multivariable logistic regression was utilized to analyze the risk and protective factors associated with mental health symptoms, with a particular focus on different types of bullying victimization.ResultsCompared to non-left-behind children (non-LBC), left-behind children (LBC) exhibited a higher prevalence of mental health issues: anxiety symptoms (24.0% vs. 18.0%, p<0.001), depressive symptoms (27.9% vs. 19.4%, p<0.001), and self-injurious behavior (17.7% vs. 12.2%, p<0.001). Among LBC, physical bullying was identified as the most significant predictor of anxiety symptoms (OR = 1.62). Additionally, LBC who experienced verbal bullying had a higher risk of depressive symptoms (OR = 2.23) and self-injurious behaviors (OR = 1.54). Enhanced family functioning, positive teacher-student relationships, and strong peer relationships were found to offer protective effects against mental health problems.ConclusionOur results suggested that LBC experienced a higher incidence of mental health symptoms, particularly among those who had been victims of bullying. This underscores the urgent need for supportive strategies focused on the school environment and interpersonal relationships to mitigate negative mental health outcomes for LBC.